KINESIOTAPING AND WOBBLE BOARD EXERCISE INCREASED SHOOTING ACCURACY IN FOOTBALL PLAYERS WITH CHRONIC ANKLE INSTABILITY - Hardi, Zhilan Zholila; Jannah, Suci Muqodimatul; Imania, Dika Rizki (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
Athletes who experience chronic ankle instability (CAI) will have a disturbance in balance that affects the accuracy of kicking the ball toward the goal. The Kinesio taping and wobble board exercise intervention can significantly improve balance, however, its effect on increasing shooting accuracy was not yet known. This study aimed to investigate the effect of kinesiotaping and wooble board exercise in increasing shooting accuracy of football players with CAI. This was an experimental study with one group pretest-postest design. A total of 7 samples were determined using the purposive sampling technique to receive Kinesio taping (KT) and wobble board exercise (WB). The kicking accuracy test was used before and after intervention to evaluate kicking accuracy. This study found that there was a significant difference in shooting accuracy score before and after intervention indicating that the intervention increased shooting accuracy. Further research is expected to add the number of samples and pay attention to the length of experiencing CAI.